2018
DOI: 10.1016/j.apgeochem.2017.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Using Local Moran's I to identify contamination hotspots of rare earth elements in urban soils of London

Abstract: Highlights Local Moran's I is used to identify contamination hotspots of REEs in urban soils. Several areas in London soils had elevated concentrations of Ce, La, Nd, Sc, Sm, Yb and Y. Soil parent material was the natural factor leading to enrichment of REEs in some areas. Possible anthropogenic sources include fertilizer, industries activities and vehicular emission. AbstractRare earth elements (REEs) in urban soils are receiving more attention because of their increased use in modern technology. Up to no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(39 citation statements)
references
References 77 publications
1
35
0
3
Order By: Relevance
“…Therefore, as previous studies found that GCMs in NMME generate skilful forecasts of ENSO (e.g. Kirtman et al, 2014;Saha et al, 2014;Zhang et al, 2017), Fig. 6 suggests that the skill, as is indicated by anomaly correlation, of GCM forecasts in NMME can also be related to ENSO.…”
Section: Frequency Of Case Hh In Son Djf and Mamsupporting
confidence: 59%
See 2 more Smart Citations
“…Therefore, as previous studies found that GCMs in NMME generate skilful forecasts of ENSO (e.g. Kirtman et al, 2014;Saha et al, 2014;Zhang et al, 2017), Fig. 6 suggests that the skill, as is indicated by anomaly correlation, of GCM forecasts in NMME can also be related to ENSO.…”
Section: Frequency Of Case Hh In Son Djf and Mamsupporting
confidence: 59%
“…forecast-oriented low ocean resolution (Vecchi et al, 2014;Jia et al, 2015). Thirdly, there are substantial regional variations, possibly due to the predictability of seasonal precipitation (Doblas-Reyes et al, 2013;Becker et al, 2014;Zhang et al, 2017). For example, orange regions cover large parts of Australia, in particular south-western and south-eastern Australia.…”
Section: Spatial Clustering In Jjamentioning
confidence: 99%
See 1 more Smart Citation
“…In Eq. 6 Adding to the global Moran's I, the local Moran's I is obtained to test whether ri at a certain grid cell i significantly relates to surrounding rj at the local scale [Anselin, 2006;Hao et al, 2016;Yuan et al, 2018] ( ) ( )…”
Section: Methodsmentioning
confidence: 99%
“…This means that the farther apart the two spatial units are, the weaker the spatial association is, which is consistent with Tobler's first law of geography. Therefore, this type of weight is widely used in the research of various spatial relationships [49,50]. In this study, an inverse distance weight was established, which added the limitation of K-nearest neighbors (K is a positive integer) to control the minimum number of neighbors in each province [51].…”
Section: Geographic Distance Weight (Geo-distance Weight)mentioning
confidence: 99%